Concrete modified by concrete internal curing agent

Through hollow nanosilica particles modified aramid nanofiber gel, the problems of strain softening and low mechanical properties of internal curing agents of traditional fiber concrete under tensile action are solved, and the bending strength and tensile cleavage of concrete are improved. Cracking strength extends service life and optimizes water retention performance.

CN118812184BActive Publication Date: 2024-12-27SUZHOU CHUXIN MOYI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270673.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Traditional fiber concrete has strain softened under tensile action, which cannot effectively limit the development of cracks. The mechanical properties of internal curing agents are low, resulting in insufficient durability and strength of concrete, especially in harsh environments.

Method used

Hollow nanosilica particles modified aramid nanofiber gel is used as the internal curing agent for concrete. The fiber adhesion is improved through electrostatic action and sodium silicate adhesion mechanism, inhibit the shrinkage of the water release volume of the internal curing agent, and enhance the bending resistance of concrete. Strength and tensile splitting strength.

Benefits of technology

It significantly improves the stability and uniform properties of concrete, enhances the bending strength and tensile splitting strength, extends the service life, and optimizes the water retention performance of the internal curing agent, avoiding the complex crosslinking process in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812184B_ABST
    Figure CN118812184B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of concrete materials, and specifically relates to a concrete internal curing agent modified concrete. The preparation method of the internal curing agent comprises the following steps: (1) preparing hollow nano-silica particles; (2) preparing aramid nano-fiber dispersion; (3) sequentially adding hollow nano-silica particles and deionized water to the aramid nano-fiber dispersion to obtain a mixed solution; (4) steam bath treatment and freeze drying to obtain a concrete internal curing agent. Using hollow nano-silica particles to modify aramid nano-fiber gel as a concrete internal curing agent can inhibit the volume shrinkage of the internal curing agent after water release, thereby improving the strength and durability of the concrete. The vapor of the protonated solvent protonates the aramid nano-fibers in the solution, and the gel preparation process is simple and efficient, avoiding the complex cross-linking process in the direct preparation of gel compounds by the traditional method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials, and in particular relates to concrete modified by a concrete internal curing agent. Background Art

[0002] In view of the poor durability, insufficient toughness, low tensile strength and poor deformation capacity of concrete, fibers are generally added to improve the toughness and crack resistance of concrete. With the development of production and life, while improving toughness, new requirements are put forward for the tensile deformation capacity and crack control ability of concrete. In the face of some harsh environments in nature (alpine areas, marine environments, etc.), concrete must not only pursue the enhancement of toughness, tensile strength and deformation capacity, but also take into account the improvement of strength and durability.

[0003] The superposition effect of "compounding" is the key to improving material performance. After compounding, the material can not only retain the original excellent performance of the material (such as high toughness, high deformation capacity, etc.), but also improve or even eliminate the material's poor performance (such as low strength, low durability, etc.). For traditional reinforced concrete materials, the steel bars only have a restraining and reinforcing effect on the concrete material at the macro level, and have little effect on the concrete at the micro level.

[0004] Benefiting from the influence of the "composite" theory, combined with the idea of ​​concrete reinforcement, the concrete material is evenly reinforced by adding fibers, and the bonding effect between the fibers and the concrete matrix is ​​used to restrain the deformation and cracking of the concrete, thereby enhancing the strength, toughness and durability of the material at the micro level. Compared with ordinary concrete, the toughness and crack resistance of traditional fiber concrete have been greatly improved, but due to the insufficient deformation capacity of the added fibers, traditional fiber concrete only shows a reduction in early cracks and an increase in toughness. Under direct tensile action, it usually shows strain softening behavior and cannot limit the development of cracks.

[0005] Internal curing technology can reduce shrinkage cracking of concrete and improve the durability of concrete. Shrinkage cracks are one of the main reasons for the reduction of concrete durability, and hydration internal curing technology can reduce shrinkage cracks, improve concrete durability and extend its service life. It can reduce concrete consumption and is one of the effective ways to reduce carbon emissions in the construction industry. However, the internal curing agent prepared by the existing technology has low mechanical properties. After absorbing water, its volume will reach several times its original size, and after releasing water, it will shrink in volume, which will increase the total porosity of cement. Although the capillaries and gel pores in the concrete are effectively reduced due to the internal curing effect of the internal curing agent, compensating for the compressive strength of the concrete, the holes caused by this expansion and contraction still have a certain impact on the strength of the concrete. Summary of the invention

[0006] In view of the above problems, the main purpose of the present invention is to provide a concrete curing agent modified concrete.

[0007] The technical solution adopted by the present invention is: a concrete internal curing agent modified concrete, the mass ratio of cement and internal curing agent in the concrete is (600-650): (1-10); the preparation method of the concrete internal curing agent comprises the following steps:

[0008] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0009] (2) placing aramid fibers into a reaction kettle containing alkali and dimethyl sulfoxide and stirring the mixture to prepare an aramid nanofiber dispersion;

[0010] (3) adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, and stirring for 1-8 hours to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:(0.5-8);

[0011] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent.

[0012] The use of hollow nano-silica particles to modify aramid nanofiber gel as an internal curing agent for concrete can not only give play to the water absorption and water retention effect of the gel, but more importantly, the hollow nano-silica particles to modify the rigid aramid nanofiber as a gel skeleton can inhibit the volume shrinkage of the internal curing agent after water release, thereby improving the strength and durability of the concrete. In previous work, the inventor used nano-calcium carbonate modified by a coupling agent as an enhancing and modifying auxiliary agent for aramid fiber. Although the water absorption and water loss stability of the internal curing agent were improved to a certain extent, the above process was complicated, and the binding force between calcium carbonate and aramid nanofiber was weak, and it was easy to fall off during the water absorption and water release process of the gel, which reduced the mechanical strength of the gel network. The present invention introduces hollow silica microspheres to reinforce aramid nanofiber gel. On the one hand, the surface of the hollow nano-silica particles prepared by the template process has a certain positive charge; while the aramid nanofiber prepared by the alkali solution method has a certain negative charge. Under the action of static electricity, the hollow nano-silica particles will be adsorbed to the surface of the aramid nanofiber, thereby improving the adhesion of the particles. On the other hand, in an alkaline environment, a layer of sodium silicate will slowly form on the surface of silica, which not only prevents further corrosion from the alkali solution, but is also an excellent inorganic adhesive that can effectively adhere to the surface of aramid nanofibers to improve adhesion. The introduction of hollow silica eliminates the need for complex coupling modification processes, which not only disperses the stress on the gel and enhances the mechanical properties of the gel, but also reduces the density of the gel composite material, allowing it to be evenly distributed in the concrete under the action of buoyancy, thereby improving the stability and uniformity of the concrete to a certain extent, and achieving an increase in the flexural strength and tensile splitting strength of the concrete.

[0013] Furthermore, the specific preparation process of the hollow nano-silica particles in step (1) is as follows:

[0014] S1, dispersing nano-polystyrene and ammonia water in a mixed solution of ethanol and deionized water;

[0015] S2, adding ethyl orthosilicate to the mixed solution, stirring and reacting at 45-55°C for 10-20h;

[0016] S3, after centrifugation, washing, drying and calcination, hollow nano-silica particles are obtained.

[0017] Furthermore, the particle size of the nano-polystyrene is 100-300 nm.

[0018] Furthermore, the mass concentration of the ammonia water is 15-20%; the mass volume ratio of the nano-polystyrene, ammonia water and tetraethyl orthosilicate is 1g: (0.1-0.6)g: (2-5)mL.

[0019] Furthermore, the washing is performed by alternating washing with deionized water and ethanol.

[0020] Furthermore, the calcination temperature is 550-650° C., and the calcination time is 6-8 hours.

[0021] Furthermore, in step (2), the base is potassium hydroxide; the ratio of the aramid fiber, the base and the dimethyl sulfoxide is 1 g: (1-2) g: (400-500) mL; and the stirring is carried out at room temperature for 4-8 days.

[0022] Furthermore, in step (3), the stirring time is 2-5 hours, and the ratio of aramid fiber to deionized water is 1 g: (200-300) mL. By controlling the stirring time, the adhesion of hollow nano-silica can be effectively adjusted. If the stirring time is too short, the silica reaction is not sufficient and the adhesion ability of sodium silicate is reduced; if the stirring time is too long, the attached particles may fall off.

[0023] Furthermore, in step (4), the steam bath is an acetic acid steam bath or a hydrochloric acid steam bath, and the steam bath treatment time is 6-9 hours. By using a simple and low-cost steam coagulation bath, the aramid nanofibers in the solution are protonated by the steam of the protonated solvent. The gel preparation process is simple and efficient, and a physical gel material with a rich network structure can be successfully prepared under low concentration conditions. The complex cross-linking process in the direct preparation of gel compounds by the traditional method is effectively avoided, and the refinement and stability of the structure are greatly improved.

[0024] Furthermore, the concrete contains the following components in parts by weight: 150-160 parts of water, 600-650 parts of cement, 100-110 parts of fly ash, 550-600 parts of sand, 800-850 parts of crushed stone, 1-10 parts of internal curing agent, 5-10 parts of polycarboxylate water reducer, and 10-15 parts of UEA expansion agent.

[0025] The present invention has the following advantages: using hollow nano-silica particles to modify aramid nanofiber gel as an internal curing agent for concrete can not only exert the water absorption and water retention effect of the gel, but more importantly, using rigid aramid nanofibers as the gel skeleton can inhibit the volume shrinkage of the internal curing agent after water release, thereby improving the strength and durability of the concrete. On the one hand, under the action of static electricity, the hollow nano-silica particles will be adsorbed on the surface of the aramid nanofibers, thereby improving the adhesion of the particles; on the other hand, a layer of sodium silicate will slowly form on the surface of the silica in an alkaline environment, which can not only prevent further corrosion by the alkali solution, but also effectively adhere to the surface of the aramid nanofibers, thereby improving the adhesion ability. The introduction of hollow silica enhances the mechanical properties of the gel, promotes the uniform distribution of the gel material in the concrete, improves the stability and uniformity of the concrete to a certain extent, and realizes the improvement of the flexural strength and tensile splitting strength of the concrete. The aramid nanofibers in the solution are protonated by the vapor of the protonated solvent, the gel preparation process is simple and efficient, and a physical gel material with a rich network structure can be successfully prepared under low concentration conditions. The complex cross-linking process in the direct preparation of gel compounds by traditional methods is effectively avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a transmission electron microscopy image of the hollow nano-silica particles prepared in Example 6;

[0028] Figure 2 This is a scanning electron microscope image of the concrete curing agent prepared in Example 6;

[0029] Figure 3 This is a test chart of the water retention performance of the internal curing agent prepared in Examples 1-5;

[0030] Figure 4 This is a test chart of the water retention performance of the internal curing agent prepared in Examples 6-8 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The aramid fiber used in the embodiment of the present invention and the comparative example is Kevlar fiber produced by DuPont. The specific preparation process of the hollow nano-silica particles is as follows:

[0033] S1, dispersing nano-polystyrene and ammonia water in a mixed solution of ethanol and deionized water; the particle size of the nano-polystyrene is 200nm; the mass concentration of the ammonia water is 20%;

[0034] S2, adding tetraethyl orthosilicate to the mixed solution, stirring and reacting at 50°C for 16 hours; the mass volume ratio of the nano-polystyrene, ammonia water, and tetraethyl orthosilicate is 1g:0.5g:4mL;

[0035] S3, centrifugation, washing with deionized water and ethanol alternately, drying, and calcining to obtain hollow nano-silica particles; the calcination temperature is 600° C. and the calcination time is 7 hours.

[0036] Example 1

[0037] A method for preparing a concrete internal curing agent comprises the following steps:

[0038] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0039] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1g:1g:400mL; stirring is performed at room temperature for 4 days;

[0040] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 2 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:0.5; and the ratio of aramid fiber to deionized water is 1 g:200 mL;

[0041] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is a hydrochloric acid steam bath, and the steam bath treatment time is 6 hours.

[0042] The concrete comprises the following components in parts by weight: 150 parts of water, 600 parts of cement, 100 parts of fly ash, 550 parts of sand, 800 parts of crushed stone, 1 part of internal curing agent, 5 parts of polycarboxylate water reducer, and 10 parts of UEA expansion agent.

[0043] Example 2

[0044] A method for preparing a concrete internal curing agent comprises the following steps:

[0045] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0046] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1g:2g:500mL; stirring is performed at room temperature for 8 days;

[0047] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 5 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:8; and the ratio of aramid fiber to deionized water is 1 g:300 mL;

[0048] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 9 hours.

[0049] The concrete comprises the following components in parts by weight: 160 parts of water, 650 parts of cement, 110 parts of fly ash, 600 parts of sand, 850 parts of crushed stone, 10 parts of internal curing agent, 10 parts of polycarboxylate water-reducing agent, and 15 parts of UEA expansion agent.

[0050] Example 3

[0051] A method for preparing a concrete internal curing agent comprises the following steps:

[0052] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0053] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1g:1g:500mL; stirring is performed at room temperature for 8 days;

[0054] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 2 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:8; and the ratio of aramid fiber to deionized water is 1 g:300 mL;

[0055] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is a hydrochloric acid steam bath, and the steam bath treatment time is 6 hours.

[0056] The concrete comprises the following components in parts by weight: 150 parts of water, 650 parts of cement, 110 parts of fly ash, 550 parts of sand, 800 parts of crushed stone, 10 parts of internal curing agent, 5 parts of polycarboxylate water reducer, and 15 parts of UEA expansion agent.

[0057] Example 4

[0058] A method for preparing a concrete internal curing agent comprises the following steps:

[0059] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0060] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1g:2g:400mL; stirring is performed at room temperature for 4 days;

[0061] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 5 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:0.5; and the ratio of aramid fiber to deionized water is 1 g:250 mL;

[0062] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 8 hours.

[0063] The concrete comprises the following components in parts by weight: 160 parts of water, 600 parts of cement, 100 parts of fly ash, 600 parts of sand, 800 parts of crushed stone, 1 part of internal curing agent, 10 parts of polycarboxylate water reducer, and 10 parts of UEA expansion agent.

[0064] Example 5

[0065] A method for preparing a concrete internal curing agent comprises the following steps:

[0066] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0067] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.3 g:480 mL; stirring is performed at room temperature for 7 days;

[0068] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 3 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:2; and the ratio of aramid fiber to deionized water is 1 g:220 mL;

[0069] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0070] The concrete contains the following components in parts by weight: 155 parts of water, 620 parts of cement, 108 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 8 parts of internal curing agent, 8 parts of polycarboxylate water reducer, and 11 parts of UEA expansion agent.

[0071] Example 6

[0072] A method for preparing a concrete internal curing agent comprises the following steps:

[0073] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0074] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0075] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 3 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:4; and the ratio of aramid fiber to deionized water is 1 g:260 mL;

[0076] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0077] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0078] Example 7

[0079] A method for preparing a concrete internal curing agent comprises the following steps:

[0080] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0081] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0082] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 1 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:4; and the ratio of aramid fiber to deionized water is 1 g:260 mL;

[0083] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0084] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0085] Example 8

[0086] A method for preparing a concrete internal curing agent comprises the following steps:

[0087] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0088] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0089] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 8 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:4; and the ratio of aramid fiber to deionized water is 1 g:260 mL;

[0090] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0091] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0092] Comparative Example 1

[0093] A method for preparing a concrete internal curing agent comprises the following steps:

[0094] (1) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0095] (3) adding solid nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, and stirring for 3 hours to obtain a mixed solution; wherein the mass ratio of aramid fiber to solid nano-silica particles is 100:4; the ratio of aramid fiber to deionized water is 1 g:260 mL; and the diameter of the solid nano-silica particles is 200 nm;

[0096] (3) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0097] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0098] Comparative Example 2

[0099] A method for preparing a concrete internal curing agent comprises the following steps:

[0100] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0101] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0102] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 3 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:12; and the ratio of aramid fiber to deionized water is 1 g:260 mL;

[0103] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0104] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0105] Comparative Example 3

[0106] A method for preparing a concrete internal curing agent comprises the following steps:

[0107] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0108] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0109] (3) Adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, stirring for 3 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:4; and the ratio of aramid fiber to deionized water is 1 g:260 mL;

[0110] (4) Adding acetic acid solution to the mixed solution to obtain an initial hydrogel; exchanging the solvent of the initial hydrogel with deionized water to obtain a hydrogel; freeze-drying the hydrogel and crushing it to obtain a concrete curing agent.

[0111] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0112] Comparative Example 4

[0113] A method for preparing a concrete internal curing agent comprises the following steps:

[0114] (1) Preparation of hollow nano-silica particles using nano-polystyrene as template;

[0115] (2) placing aramid fiber in a reaction kettle containing alkali and dimethyl sulfoxide, stirring evenly, and preparing an aramid nanofiber dispersion; the alkali is potassium hydroxide; the ratio of the aramid fiber, alkali and dimethyl sulfoxide is 1 g:1.6 g:450 mL; stirring is performed at room temperature for 6 days;

[0116] (3) Deionized water and hollow nano-silica particles were sequentially added to the aramid nanofiber dispersion and stirred for 3 h to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles was 100:4; and the ratio of aramid fiber to deionized water was 1 g:260 mL;

[0117] (4) The mixed solution is subjected to a steam bath to obtain an initial hydrogel; the initial hydrogel is subjected to a solvent exchange with deionized water to obtain a hydrogel; the hydrogel is freeze-dried and crushed to obtain a concrete curing agent; the steam bath is an acetic acid steam bath, and the steam bath treatment time is 7 hours.

[0118] The concrete contains the following components in parts by weight: 155 parts of water, 630 parts of cement, 105 parts of fly ash, 580 parts of sand, 820 parts of crushed stone, 4 parts of internal curing agent, 7 parts of polycarboxylate water reducer, and 13 parts of UEA expansion agent.

[0119] The mechanical properties of concrete are tested according to GB / T 50081-2019; the cracking area of ​​concrete is tested according to GB / T 50082-2009.

[0120]

[0121] Figure 1 This is a transmission electron microscope image of the hollow nano-silica particles prepared in Example 6. It can be seen from the image that the particle size of the prepared hollow nano-silica particles is relatively uniform, and the wall thickness is about 15 nm. Figure 2 The scanning electron microscope image of the concrete curing agent prepared in Example 6 shows that the hollow nano-silica has a high attachment amount and is evenly attached to the surface of the aramid nanofibers, effectively preventing the agglomeration of the aramid nanofibers in the aqueous solution and improving the mechanical strength of the aramid nanofibers. Figure 3-4The water retention performance test diagram of the internal curing agent prepared in the embodiment and the comparative example shows that the internal curing agent prepared by the method of the present invention has a slow release effect and excellent water retention performance. It can be seen from Table 1 and Comparative Example 1 that, relative to solid nano-silica, the use of hollow nano-silica particles to modify aramid nanofiber gel as a concrete internal curing agent can not only play the role of water absorption and water retention of the gel, but more importantly, the use of rigid aramid nanofibers modified with hollow structure silica as the gel skeleton can inhibit the volume shrinkage of the internal curing agent after water release, thereby improving the strength and durability of the concrete. Comparative Example 2 shows that the hollow nano-silica particles cannot be too much, otherwise the gel network structure may be destroyed due to exceeding the fiber load-bearing capacity. Comparative Example 3 shows that the aramid nanofibers in the solution are protonated by the vapor of the protonated solvent, and a physical gel material with a rich network structure can be successfully prepared under low concentration conditions. It effectively avoids the complex cross-linking process in the direct preparation of gel compounds by the traditional method, and greatly improves the refinement and stability of the structure. Compared with Example 6, in step (3) of Comparative Example 4, water is first added to the aramid nanofiber dispersion and then the hollow silica nanoparticles are added. When water is added, the aramid nanofibers will agglomerate and the nanoparticles cannot effectively isolate the aramid nanofibers, affecting the improvement of the gel porosity and pore size.

[0122] Those skilled in the art will appreciate that the embodiments herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A concrete curing agent modified concrete, characterized in that: The mass ratio of cement to internal curing agent in concrete is (600-650):(1-10); the preparation method of concrete internal curing agent comprises the following steps: (1) Preparation of hollow nano-silica particles using nano-polystyrene as template; (2) placing aramid fibers into a reaction kettle containing alkali and dimethyl sulfoxide and stirring the mixture to prepare an aramid nanofiber dispersion; (3) adding hollow nano-silica particles and deionized water to the aramid nanofiber dispersion in sequence, and stirring for 1-8 hours to obtain a mixed solution; wherein the mass ratio of aramid fiber to hollow nano-silica particles is 100:(0.5-8); (4) preparing an initial hydrogel by subjecting the mixed solution to a steam bath; exchanging the obtained initial hydrogel with deionized water to obtain a hydrogel; freeze-drying the hydrogel and crushing it to obtain a concrete curing agent; In the step (3), the stirring time is 2-5 hours, and the ratio of aramid fiber to deionized water is 1 g: (200-300) mL; in the step (4), the steam bath is an acetic acid steam bath or a hydrochloric acid steam bath, and the steam bath treatment time is 6-9 hours.

2. The concrete modified concrete by the concrete curing agent according to claim 1, characterized in that: The specific preparation process of the hollow nano-silica particles in step (1) is as follows: S1, dispersing nano-polystyrene and ammonia water in a mixed solution of ethanol and deionized water; S2, adding ethyl orthosilicate to the mixed solution, stirring and reacting at 45-55°C for 10-20h; S3, after centrifugation, washing, drying and calcination, hollow nano-silica particles are obtained.

3. The concrete modified by the concrete curing agent according to claim 2, characterized in that: The particle size of the nano polystyrene is 100-300nm.

4. The concrete modified concrete by the concrete curing agent according to claim 2, characterized in that: The mass concentration of the ammonia water is 15-20%; the mass volume ratio of the nano-polystyrene, ammonia water and tetraethyl orthosilicate is 1g: (0.1-0.6)g: (2-5)mL.

5. The concrete modified by the concrete curing agent according to claim 2, characterized in that: The washing is performed by alternately washing with deionized water and ethanol.

6. The concrete modified concrete by the concrete curing agent according to claim 2, characterized in that: The calcination temperature is 550-650° C., and the calcination time is 6-8 hours.

7. The concrete modified by the concrete curing agent according to claim 1, characterized in that: In step (2), the alkali is potassium hydroxide; the ratio of the aramid fiber, the alkali and the dimethyl sulfoxide is 1 g: (1-2) g: (400-500) mL; and the stirring is carried out at room temperature for 4-8 days.